Assets of the insurance and pension sectors as a source of innovation funding - Talimova, L.A.; Kalkabaeva, G.M. (BUKETOV BUSINESS REVIEW, 2018)
The article examines the role of the pension and insurance sector in financing the innovation sector of Kazakhstan. The investment potential of the pension and insurance sectors in the development of long-term lending and investment in the Kazakh economy was analyzed. As international experience shows, the assets of the pension fund and insurance companies can be the main factor in the growth of financial markets, provided that they reach a certain level of development, the formation of infrastructure and the availability of suitable instruments for investment. At the same time, as a result of the analysis, it was revealed that an inefficient structure of the investment portfolio of the UAPF and domestic insurance companies was formed from the perspective of investing the needs of the innovative development of the economy of Kazakhstan. In order to achieve a positive dynamics of the innovation process, boost the development of high-tech industries, it is necessary to increase the volume of investment in innovation activities in the Republic of Kazakhstan. The analysis of the investment potential of UAPF and insurance companies showed that there are many problems that impede the use of its use to finance the innovation sector. The expansion of the investment policy of the pension fund and insurance companies and its reorientation towards the needs of the national economy, including the innovation sector, largely depends on the support from the state. The necessity of improving the state policy to stimulate investment in the insurance and pension sectors in innovation and create an effective system of financing the national innovation sector has been substantiated.